Exploring the work of First Nations directors of education in Manitoba - Murdock, Nora (2016)
Education for First Nations must be understood within the historical context which saw their cultural, linguistic, and traditional knowledge undermined and devalued (Final Report of the Truth and Reconciliation Commission of Canada, 2015). The conditions that exist for First Nations today are a result of First Nations people having been disadvantaged in a multitude of ways by colonization and nowhere more so than in the First Nations education system, because the structure of formal schooling has as its foundation colonial institutions (Battiste, 2013). It is for these reasons that I use a postcolonial theoretical framework to guide this study. As the education leaders in First Nations communities, I examine the nature of the work of First Nations Directors of Education working or who worked recently in First Nations band-operated on-reserve school systems in Manitoba, Canada. This qualitative research study explores selected aspects of their experiences, perspectives, preparation, and training. Through the eyes, voices, and stories of the participants, this study seeks to understand the milieu that is First Nations on-reserve education. The results of the study identify what can be done to bring about transformational change for First Nations students. The study found that the role of the First Nations Director of Education is multi-faceted and complex. The roles and responsibilities that the participants identified were categorized using Cuban’s (1988) typology of core roles: managerial, political, and instructional. Their work is influenced by many factors including underfunding, lack of resources, high teacher turnover, and the on-going impacts of the residential schools and colonialism. The study identifies the need for specific training and provides recommendations for practice and future research. October 2016